Clinical validation of factors associated with sedentary lifestyle in adolescents - Guedes, Nirla Gomes (2019)
Objective: to validate clinically the factors associated with nursing diagnosis sedentary lifestyle in adolescents. Methods: a cross-sectional study, developed with 158 adolescent students. The chi-square test was used to identify the association between the presence of sedentary lifestyle and associated factors. The level of significance was set at p<0.05. Results: the prevalence of sedentary lifestyle was 68.3%. The presence of associated factors such as poor knowledge about the benefits that physical activity brings to health and/or the consequences of physical inactivity, lack of resources for the practice of physical exercise, insufficient training to exercise and intolerance to activity increased the likelihood of presence of sedentary lifestyle (p<0.05). Conclusion: the nursing diagnosis sedentary lifestyle was prevalent among adolescents and there are specific factors that intensify the probability of developing this diagnosis.